Large Tumefactive IgG4-related Disease: Histologic, Cytologic, and Immunohistochemical Features of a Very Unusual Case. Issue 3 (March 2020) - Akhtar, Israh; Shenoy, Veena; Khan, Majid; Saad, Ali G.
Abstract : Immunoglobulin G4-related disease (IgG4-RD) is a regional or systemic multiorgan lymphoplasmacytic inflammatory disease of unknown etiology. It has been described in numerous organs and anatomic locations. Review of the literature shows that when the disease involves the retroperitoneum it causes retroperitoneal fibrosis. Tumefactive IgG4-RD of the retroperitoneum has not been previously reported. In this report, we describe the first case of a large retroperitoneal tumefactive IgG4-RD along with its histologic, cytologic, and immunohistochemical characteristics.